2015
DOI: 10.1210/jc.2015-1343
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile GnRH Is Superior to hCG in Therapeutic Efficacy in Adolescent Boys With Hypogonadotropic Hypogonadodism

Abstract: Boys with HH may be effectively treated with GnRH. We suggested that GnRH exhibits higher efficacy in treating adolescent boys with HH than hCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 22 publications
0
38
0
2
Order By: Relevance
“…Previous studies, including a small number of prepubertal HH boys, have demonstrated the ‘proof of principle’ that hCG induces a rise in serum testosterone levels, resulting in virilization, and that hCG combined with FSH stimulates testicular growth and activates spermatogenesis in adolescents . Table provides an overview on these studies, in comparison with our study.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies, including a small number of prepubertal HH boys, have demonstrated the ‘proof of principle’ that hCG induces a rise in serum testosterone levels, resulting in virilization, and that hCG combined with FSH stimulates testicular growth and activates spermatogenesis in adolescents . Table provides an overview on these studies, in comparison with our study.…”
Section: Discussionmentioning
confidence: 58%
“…Virilization in adolescents or young adults can also be achieved with pulsatile GnRH [186][187][188] or gonadotropin therapy (hCG alone or combined with FSH). 189,190 These fertility-inducing treatments stimulate endogenous testosterone (and estradiol) production by testicular Leydig cells and are associated with good physical and psychological outcomes.…”
Section: Induction Of Male Sexual Characteristicsmentioning
confidence: 99%
“…The detection method of hormones, hCG standard and prolonged stimulating test and LHRH stimulation test were referred to the published literature of our group [15][16].…”
Section: Methodsmentioning
confidence: 99%